Exploring the role of tumour microenvironment in the behaviour of breast ductal carcinoma in situ - Toss, Michael Salah Shawky (2020)
Background: Breast ductal carcinoma in situ (DCIS) accounts for more than 20% of screen-detected breast cancer. To date, predictors of DCIS behaviour are not well defined. Tumour microenvironment (TME) plays a role in tumour progression; therefore, the aim of the current study was to characterise a large cohort of DCIS with long term follow-up data and to decipher the role of TME in DCIS outcome.